Pengaruh Stres Kerja terhadap Burnout dengan Resilience sebagai Variabel Mediasi pada Perawat di RSUD dr. Achmad Darwis Kabupaten Lima Puluh Kota - Rifatul Husna; Rini Sarianti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of work stress on burnout in nurses, considering the mediating role of resilience. This research uses a quantitative approach with a survey method, involving 82 inpatient nurses as respondents. Data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM–PLS) method through the SmartPLS 4 application. The research results indicate that work stress has a positive and significant effect on burnout, and a negative and significant effect on resilience. Resiliencealso has a significant negative impact on burnout and is proven to significantly mediate the relationship between work stress and burnout. This finding confirms that resilience is an important factor in reducing the risk of burnout in nurses facing high work pressure. Therefore, increasing nurses' resilience is an important strategy in overcoming burnout at RSUD dr. Achmad Darwis.